Penerapan REST API pada Aplikasi Antarmuka Alat Pemantauan Tambak Udang - Abdul Aziz, Fiqri; Subandri, M. Asep; Armada (Indonesian Society of Applied Science, 2025)
Increasing shrimp pond productivity is a top priority in fisheries cultivation, especially with the challenge of maintaining water quality as a determining factor for success. The use of modern technology such as the Internet of Things (IoT) allows the integration of monitoring tools with software-based interface applications. This study aims to develop a shrimp pond monitoring tool interface application that uses REST API to connect IoT devices with a Flutter-based application system. The methods used include software development using prototyping with a system design approach based on evaluations received from users to obtain results that meet user needs. The data obtained is sent to Firebase via REST API and displayed in real-time on a Flutter-based application. The results of the study show that the application of REST API allows faster and reliable data transmission between IoT devices and interface applications. The REST API achieved an average response time between 70–87 ms with 0% packet loss during 10-minute testing using Apache JMeter. The monitoring sensors reached accuracy levels of 93.3–96.0% for temperature and 93.7–96.4% for pH measurements. The resulting application makes it easy for users to monitor pond conditions in real-time via mobile devices. This technology supports faster pond management by delivering accurate information. This research is expected to be the basis for further development of IoT-based pond monitoring systems, focusing on improving system features and reliability to support the sustainability of shrimp pond cultivation.